Investigation of membrane fouling using molecular dynamics simulation - Ma, Yunqiao (Nanyang Technological University, 2022)
For the past few decades, tremendous progress has been made in the field of membrane technology, for the usage in water purification, pharmaceutical separation, and many other processes. The revolutionary technology of membrane filtration has out-performed conventional ones thanks to its advantages like lower energy and maintenance cost, easiness of scale-up, etc. Nevertheless, until today, membrane fouling still remains a tremendous obstacle in the implementation of membrane technology, which has motivated the use of a wide range of experimental techniques to study fouling behavior in the past decades. However, molecular-level insights, which underlie the macroscopic observable phenomena, remain incomplete. With the rapid advancement of computational power, molecular dynamics (MD) simulation has become increasingly popular to explore the interaction occurring at the ternary interface (i.e., foulant, membrane and solvent) by using explicit atom representations. MD studies have quantified interfacial physical properties and generated MD trajectories for direct visualization of the adsorption process. Therefore, it serves as an important supplement to experiments since it can easily overcome the scale limitation that limits the application range and resolution of conventional laboratory techniques. However, the usage of MD in membrane fouling field is relatively sparse compared to other domains. Thus, our group has dedicated great effort to apply MD in various fouling systems, and obtained fruitful molecular-level insights that form this thesis. This thesis is built with a structure of following: A comprehensive literature review focusing on past MD studies for membrane fouling and related foulant adsorption processes is conducted first. Next, a few studies related to using MD simulation for fouling investigation are presented. Specifically, we have investigated the following topics: (i) removal of key natural organic matters by dynamic membrane made from heated aluminium oxide particles which mitigates the downstream reverse osmosis fouling; (ii) the importance of local interaction in protein fouling under different feed conditions; (iii) relative flux trend of surfactants carrying different charges, and mechanisms underlying the surprising flux enhancement phenomenon of positively charged surfactant solution; and (iv) fouling in organic solvent environment as compared to that in aquatic system. Finally, considering the rapid progression of computational power and algorithm, future perspectives are proposed to enhance the value of MD as a tool for understanding and predicting membrane fouling.